2021
DOI: 10.1080/2162402x.2021.1954761
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the immune checkpoint receptors PD-1, LAG3, and TIM3 in the immune context of stage II and III gastric cancer by using single and chromogenic multiplex immunohistochemistry

Abstract: We sought to determine the clinicopathological significance of PD-1, LAG3, and TIM3 in gastric cancer (GC) by examining their expression and immune context. Immunohistochemistry (IHC) for PD-1, TIM3, LAG3, and tumor-infiltrating immune cell (TIIC) markers was performed in 385 stage II/III GCs. Epstein-Barr virus (EBV) and microsatellite stability (MSI) testing were performed for molecular classification. Chromogenic multiplex IHC (mIHC) for PD1, TIM3, LAG3, CD3, CD8, FOXP3, CD68, and cytokeratin was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 50 publications
3
38
0
Order By: Relevance
“…LAG3 expression is correlated with that of other immune checkpoints. In gastric cancer, the expression of programmed cell death protein 1 (PD-1) is positively correlated with that of LAG3 and T-cell immunoglobulin domain and mucin domain 3 (TIM3), whereas the expression of LAG3 is associated with the expression of TIM3 ( 27 ). The co-expression of LAG3 and PD1 or PD ligand 1 (PD-L1) has been proven in breast cancer.…”
Section: Lag3/fgl1 Structure and Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…LAG3 expression is correlated with that of other immune checkpoints. In gastric cancer, the expression of programmed cell death protein 1 (PD-1) is positively correlated with that of LAG3 and T-cell immunoglobulin domain and mucin domain 3 (TIM3), whereas the expression of LAG3 is associated with the expression of TIM3 ( 27 ). The co-expression of LAG3 and PD1 or PD ligand 1 (PD-L1) has been proven in breast cancer.…”
Section: Lag3/fgl1 Structure and Expressionmentioning
confidence: 99%
“…The single expression of LAG3 + and the dual expression of PD-1 + /LAG3 + predict better PFS, and the dual expression of TIM3 + /LAG3 + predict better OS and PFS. Furthermore, in advanced gastric cancer, a higher ratio of LAG3 + CD4 + /CD4 + T cells and LAG3 + CD8 + /CD8 + T cells is associated with better prognosis, although, at the invasive tumor margin, higher LAG3 expression is associated with better prognosis ( 27 ). In FGL1 + gastric cancer, where a higher expression of FGL1 is positively associated with gastric cancer stage and lymph node metastasis, as well as the poor OS ( 44 ).…”
Section: Clinical Application Of Lag3/fglmentioning
confidence: 99%
See 1 more Smart Citation
“…A new phase I/II clinical trial (NCT03459222) was recently opened to investigate the efficacy of co-targeting LAG-3, PD-1, and CTLA-4, which, by further enhancing the efficacy of single and double targeting approaches, might become a novel combinatorial strategy for cancer treatment in the near future. In this context, it is noteworthy that PD-1, LAG-3, and TIM-3 expression is coordinately increased in gastric cancer patients with better disease prognosis [ 185 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many patients do not experience good clinical outcomes because of tumor heterogeneity. Therefore, we also compared the expression of ICI-related genes ( PD1, CTLA4, LAG3, PD-L1, and HAVCR2 ) between the high- and low-risk groups [ 57 59 ] and found that PD1 , CTLA4, and LAG3 were significantly increased in the low-risk group, suggesting that the low-risk patients might have a better response to ICI therapy. We confirmed this using TCIA, finding that the low-risk group had a higher immunophenoscore for PD-1 inhibitor alone or the combination of PD1 and CTLA4 inhibitor.…”
Section: Discussionmentioning
confidence: 99%